Case Report: Primary intestinal histiocytic sarcoma in a cat - Pérez, Andrea; Clanxet, Jordi; Clemente-Vicario, Francisco; Puig, Jordi; Feo, Luis (Frontiers in Veterinary Science, 2026)
Histiocytic sarcoma (HS) is a rare and aggressive tumor in cats, usually presenting in a multicentric or disseminated form, with gastrointestinal involvement mainly reported as part of a metastatic disease. This report describes the first documented case of a primary intestinal HS in an 11-year-old male neutered domestic short-haired cat, presenting with acute gastrointestinal signs. Diagnostic workup included ultrasonography, cytology, histopathology, and immunohistochemistry (IHC), which confirmed a histiocytic origin through Iba-1, CD204 and MHC-II positivity and MUM1, CD117 and Desmin negativity. The patient underwent surgical excision via enterectomy, followed by adjuvant lomustine chemotherapy, achieving complete remission. Despite transient chemotherapy-induced myelosuppression, the cat remains alive and disease-free 2 years after diagnosis. This case highlights the importance of combining imaging, histopathology, and IHC when diagnosing feline intestinal masses.